The Preservation Strategy of Written Batik as a Cultural Heritage (Case Study Of GunawanSetiawan Batik in Kauman Batik Tourism Village, Solo –Central Java, Indonesia) - Mifta Khusnul Nurjanah; Abdul Rahman; - Nurhadi (LPPM Universitas PGRI Sumatera Barat, 2021)
Batik, with a unique style, reflectsthe prosperityofIndonesian culture. UNESCO officially designated batik as an Intangible Cultural Heritage of Humanity. One of the batiksin Indonesia is original hand-written batik.Batik Gunawan Setiawan is a local batik company remainsproducing traditional hand-written batik. Hand-made batikfaced few problems includingless competitive with printingbatik, scarce raw materials, and the lack of batik artist regeneration. Thisresearch aims to describe Gunawan Setiawan's Batik strategyfor maintainingsustainable written batikbusiness. This study uses structural functionaltheorydeveloped by Talcott Parsons. This is a qualitativestudy supported bya case study approach. The data were collected through in-depth interview, observation, and documentation. Data validity was tested with source triangulation. Afteranalyzing datawith data reduction, presentation, and conclusion, fact-findings indicate that to preserve written batikthe current strategycovers batik training program, writtenbatik fashioninnovation, batik-linked socialevents, direct selling promotion, mixed social media branding, joint Kauman batik tourism village,and regular Kauman batik exhibitionin Solo Batik Museum.